Cladribine and low-dose cytarabine alternating with decitabine as front-line therapy for elderly patients with acute myeloid leukaemia: a phase 2 single-arm trial. Issue 9 (September 2018) - Kadia, Tapan M; Cortes, Jorge; Ravandi, Farhad; Jabbour, Elias; Konopleva, Marina; Benton, Christopher B; Burger, Jan; Sasaki, Koji; Borthakur, Gautam; DiNardo, Courtney D; Pemmaraju, Naveen; Daver, Naval; et al.
Summary: Background: Front-line therapy for elderly or unfit patients with acute myeloid leukaemia (AML) remains unsatisfactory with poor outcomes and excessive toxicity. We studied a new low-intensity regimen of cladribine combined with low-dose cytarabine alternating with decitabine, aimed at improving outcomes in this population. Based on our previous experience, we hypothesised that this combination would be safe and more effective than current approaches with hypomethylating agents. Methods: In this single-arm, open-label, single-centre phase 2 study, we enrolled patients aged 60 years or older with previously untreated AML or high-risk myelodysplastic syndrome who had adequate organ function and an Eastern Cooperative Oncology Group performance status of 2 or less. Patients were treated with cladribine plus low-dose cytarabine for two 28-day cycles alternating with decitabine for two 28-day cycles, for up to 18 cycles. Induction therapy (cycle 1) consisted of cladribine 5 mg/m 2 intravenously over 1–2 h on days 1–5 and cytarabine 20 mg subcutaneously twice daily on days 1–10. Patients who had remission during this induction regimen moved on to consolidation therapy (cladribine 5 mg/m 2 intravenously over 1–2 h on days 1–3 and cytarabine 20 mg twice daily on days 1–10, alternating with decitabine 20 mg/m 2 intravenously on days 1–5). The primary outcome measure was disease-free survival. Secondary outcomes were overall survival, proportion of patients achieving complete response, proportion of patients achieving response, toxicity, and induction mortality. All treated patients were included in the analyses. This trial is ongoing and is registered withClinicalTrials.gov, numberNCT01515527 . Findings: Between Feb 17, 2012, and July 6, 2017, 118 patients were enrolled and treated, among whom 48 (41%) had an adverse karyotype, 20 (17%) had therapy-related AML, 18 (15%) had treated secondary AML, and 20 (17%) had TP53 mutations. Median disease-free survival was 10·8 months (IQR 5·4–25·9). 80 (68%) patients achieved objective response: 69 (58%) achieved a complete response and 11 (9%) patients had complete response with incomplete count recovery. The median overall survival was 13·8 months (6·9–28·6). The regimen was well tolerated, with one (1%) death within the first 4 weeks and eight (7%) deaths within the first 8 weeks. The most common non-haematological adverse events of grade 3 or worse were infection (88 [75%] patients), elevated total bilirubin (26 [22%] patients), rash (13 [11%] patients), and nausea (13 [11%] patients). Interpretation: The combination of cladribine and low-dose cytarabine alternating with decitabine appears to be a safe and highly effective regimen for the treatment of elderly or unfit patients with newly diagnosed AML. Further testing of this regimen is warranted, and could help to provide a new, effective option for reduced-intensity therapy in this population. Funding: Part supported by the National Institutes of Health.